Impact Of Accented Speech On The Credibility Of International Exchange Courses; Challenges For Exchanging Knowledge And Experience In The Erasmus + Program - Schmidt Oorbeek (International Conference on Coastal and Delta Areas, 2017)
Rotterdam University of Applied Science(RUAS) and Sultan Angung Islamic University (UNISSULA) have established a professional exchange program, stimulating staff mobility and student mobility. While these exchanges have enriched our educational program, students report difficulty with processing information from the non-native English speaking lecturers.Speakers with a (heavy) accent are sometimes perceived as part of an out-group. Even without prejudice about out-group members, this has a negative impact on the credibility of the received information. The influence of accent on credibility poses a challenge on our exchange program, both for students and lecturers.In this article, several suggestions to a different approach are mentioned. First of all, the credibility challenge needs to be recognized.Futhermore, a program and famework for intercultural competence could provide students with tools to improve communication and cooperation. Lastly, students may demonstrate a more positive attitude and affect when listening to friends, compared to lecturers. The opportunities for student mobility should be maximized. This article explores the impact of accented speech and the challenges this presents to the exchange program of RUAS and UNISSULA, and gives suggestions to improve the benefits from student mobility and staff mobility. Keywords: education, international exchange, accented speech